Development And Evaluation Of A Guideline On Potassium Chloride Intravenous Supplementation: Effectiveness, Safety And Cost Implications - Hirman, Melissa Mohammad (2022)
The concentrated potassium chloride injection used in intravenous supplementation of potassium in hypokalemia is associated with risks of hyperkalemia and medication error. This study aimed to develop a guideline on potassium chloride intravenous supplementation with the emphasis of using premixed formulations and evaluate its safety, effectiveness and cost implications. In Phase I of this study, a nationwide survey was conducted among 207 Malaysian hospital physicians. The findings suggested that there were variations in Malaysian physician’s prescribing practice of intravenous potassium supplementation in the treatment of hypokalemia. Data analysis revealed different physicians background resulted in different prescribing practices which may be due to the complexity of patient’s clinical conditions and medications. This poses a challenge for prescribers to treat hypokalemia and supports the need to have a practical or general guideline that can be used under different clinical conditions. This survey also revealed that Malaysian physicians favoured premixed potassium chloride formulations where physicians find it would ease usage and is safer for the patient. In Phase II of this study, a guideline with emphasis of premixed formulations was developed and implemented in a private hospital.